Application of Polymer Inclusion Membrane in the Transport of Malachite Green Dye Using Copolymer(Eugenol-Diallyl Phthalate) 2% as a Carrier - Rusyda Maulida Khairati; Agung Abadi Kiswandono; Rinawati Rinawati; Dwiky Ihwan Ma'ruf (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Malachite green is a compound commonly used as a dye for silk, leather, wool, cotton, and paper. Additionally, malachite green is utilized as a bacterial stain in microscopic analysis of cells and tissues. This study explores the transport of malachite green using the 2% copolymer of eugenol-diallyl phthalate (Co-EDAF) with the Polymer Inclusion Membrane (PIM) method. Several parameters influencing the transport of malachite green were investigated, including the pH of the source phase, HNO3 concentration in the receiving phase, PIM membrane thickness, and transport duration. The PIMs were prepared by dissolving the carrier 2% Co-EDAF, polyvinyl chloride (PVC), and dibenzyl ether (DBE) in tetrahydrofuran (THF). The concentration of malachite green after transport was measured using UV-Vis spectrophotometry at a wavelength of 613 nm. The results showed that the PIM with 2% Co-EDAF effectively transported malachite green with an efficiency of 91.30% under optimal conditions: source phase pH of 9, HNO3 concentration of 0.75 M, PIM membrane thickness at T54, and transport duration of 18 hours.